The effect of the 2004 and 2007 EU enlargement on the Spanish labour market - de la Rica, Sara (Bonn, 2009)
"The 2004 and 2007 EU enlargement has led to a significant increase in the immigration flow to Spain. Individuals from the new-EU-12 countries accounted for no more than 10% of the whole Spanish immigrant population in 2004, but by 2008 they accounted for almost 20% of the total flow of immigrants. As of 2008, immigrants from Bulgaria, Poland and Rumania account for 97 percent of new-EU-12 immigrants. These immigrants are younger, and the vast majority of them are educated to secondary level. Their employment rate is higher than that of natives, but they are hit harder by unemployment than natives. Our results point to two conclusions from a policy prospective: first, the EU enlargement has significantly improved legal immigration from new-EU-12 countries. Second, the lack of employment assimilation in terms of job quality for workers from the new-EU-12 countries may discourage the entrance of highly qualified workers. The Spanish authorities should provide on-the-job training for these qualified workers so that they can find adequate job prospects in Spain and decide to stay. "